PEMBUATAN MODUL HASIL INVENTARISASI JAMUR MAKROSKOPIS DI GUNUNG RAYAP PADA MATERI JAMUR - Iin, Yesi; Ariyati, Eka; Yeni, Laili Fitri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to create learning media such asmodulefrom the inventory of macroscopic mushrooms which later validated to determine the feasibility of media moduleas a in material of fungi at 10th Grade Senior High School based on results from macroscopic mushrooms inventory and to determine the types of makrofungi which were available in Gunung Rayap Kecamatan Kembayan Kabupaten Sanggau. The research was quantitative descriptive in format. Samples were taken using purposive sampling with cruising method. The results of the research found as many as 53 types of fungi from 2 divisions (Basidiomycota and Ascomycota) and 26 families. Validation module was done by 2 lecturer FKIP Untan and 3 high school teachers around in Gunung Rayap Kecamatan Kembayan. Based on validator assessment, media module was declared valid with the value of each Content Validity Ratio (CVR) and CVI vaules are valued 0,96 in number, so it could be used as learning media for mushrooms study. Keywords: Inventory, Macroscopic Mushrooms, Module